1998
DOI: 10.1177/0148607198022004199
|View full text |Cite
|
Sign up to set email alerts
|

Metabolic Effects of Adjuvant Recombinant Human Growth Hormone in Patients With Continuing Sepsis Receiving Parenteral Nutrition

Abstract: Before rhGH, the patients were hyperinsulinemic (mean, 44.4 mU/L) but had growth hormone levels within the normal range (< 10 mU/L). After the seventh dose of rhGH, nocturnal growth hormone concentrations rose to a mean of 35.3 +/- 26.1 and 61.3 +/- 21.05 mU/L for the low and higher dose groups, respectively. Morning IGF-1 concentrations showed a small increase during treatment, rising from a mean of 241.3 +/- 99.0 to 301.7 +/- 167.3 ng/mL for the low-dose group and from 214.5 +/- 74.6 to 294.1 +/- 116.9 ng/mL… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

1999
1999
2011
2011

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…However, neither control or septic rats treated with rhGH for 5 days showed a significant increase in plasma IGF‐1. This observation is potentially explained by the effects of nutrient intake and the septic response on the GH/IGF‐I axis and is consistent with the results of others 20,29 …”
Section: Discussionsupporting
confidence: 92%
“…However, neither control or septic rats treated with rhGH for 5 days showed a significant increase in plasma IGF‐1. This observation is potentially explained by the effects of nutrient intake and the septic response on the GH/IGF‐I axis and is consistent with the results of others 20,29 …”
Section: Discussionsupporting
confidence: 92%
“…Recombinant human GH (rhGH), with the same molecular constitution and characteristics as GH, is reported to promote protein synthesis, to potently correct negative nitrogen balance, and to improve nutrition effectively (Bettany et al 1998, Barry et al 1999, Zhu et al 2004. rhGH is widely accepted clinically to treat severe malnutrition caused by non-malignant diseases (Blake 1995, Waters et al 1996, Zhu et al 2004.…”
Section: Introductionmentioning
confidence: 99%
“…In one study, rhGH was shown to reduce net protein catabolism significantly and lower the mean systolic and diastolic pressures in five septic surgical patients requiring parenteral nutrition [39]. A similar study in eight patients, however, failed to show any significant difference in whole-body protein turnover with a 1-week course of rhGH [40]. In a randomized study of septic patients requiring intensive care support, 3 days of rhGH administration led to improved nitrogen balance, but the positive effects were lost following the end of treatment [41].…”
Section: Administration Of Growth Factorsmentioning
confidence: 99%